Expanded Clinical Pharmacogenetics Implementation Consortium Guideline for Medication Use in the Context of G6PD Genotype. Issue 5 (24th September 2022) - Gammal, Roseann S.; Pirmohamed, Munir; Somogyi, Andrew A.; Morris, Sarah A.; Formea, Christine M.; Elchynski, Amanda L.; Oshikoya, Kazeem A.; McLeod, Howard L.; Haidar, Cyrine E.; Whirl‐Carrillo, Michelle; Klein, Teri E.; Caudle, Kelly E.; et al.
Abstract : Glucose‐6‐phosphate dehydrogenase (G6PD) deficiency is associated with development of acute hemolytic anemia in the setting of oxidative stress, which can be caused by medication exposure. Regulatory agencies worldwide warn against the use of certain medications in persons with G6PD deficiency, but in many cases, this information is conflicting, and the clinical evidence is sparse. This guideline provides information on using G6PD genotype as part of the diagnosis of G6PD deficiency and classifies medications that have been previously implicated as unsafe in individuals with G6PD deficiency by one or more sources. We classify these medications as high, medium, or low to no risk based on a systematic review of the published evidence of the gene–drug associations and regulatory warnings. In patients with G6PD deficiency, high‐risk medications should be avoided, medium‐risk medications should be used with caution, and low‐to‐no risk medications can be used with standard precautions, without regard to G6PD phenotype. This new document replaces the prior Clinical Pharmacogenetics Implementation Consortium guideline for rasburicase therapy in the context of G6PD genotype (updates at: www.cpicpgx.org ).